Nation-wide cohort of device-measured sedentary time and physical activity in the USA—the Cancer Prevention Study-3 (CPS-3) Accelerometry Substudy: cohort profile - Erika Rees-Punia; Alpa Patel; Jillian Nelson; Peter J Briggs; Nance Joiner; James M Hodge; Jeuneviette E Bontemps-Jones; Den E Bloodworth; Ashley Yeager; Jeshondria McCrary (BMJ Open)
Purpose This paper describes the data collection and management methods for the Cancer Prevention Study-3 (CPS-3) Accelerometry Substudy, a nested cohort of device-based physical activity and sedentary time data.Participants US-based CPS-3 participants (initially enrolled 2006–2013) who completed the 2018 follow-up survey and had a valid email address were invited to the Accelerometry Substudy (n=109 780). Among the 23 111 participants who registered and were shipped an ActiGraph GT3X+ accelerometer, 21 219 participants returned the device with a complete wear log (91.8%) and 20 950 (90.6%) provided at least three adherent days of data (eg, days with at least 10 hours of wear).Findings to date Participants with ≥3 adherent days were predominantly female (n=16 187, 77.3%), non-Latino white (n=17 977, 85.8%) and had an average age of 58 years (SD=9.8). The median daily wear time was 15.3 hours, which did not vary considerably by wear day. The median time spent in moderate-intensity aerobic physical activity was 29 min/day (IQR=36), and the median time in vigorous physical activity was 3 min/day (IQR=13). Participants were sedentary for 9.4 hours (564 min, IQR=171 min) and accumulated a median of 6474 steps per day (IQR=5348).Future plans The full CPS-3 cohort will be linked with the National Death Index and state cancer registries biennially. Participants will be sent triennial surveys for the next two decades. Future analyses within the CPS-3 Accelerometry Substudy more specifically aim to identify relationships between physical activity, sedentary time and health outcomes, primarily cancer incidence, survival and survivorship.